2018
DOI: 10.1177/1687814018814920
|View full text |Cite
|
Sign up to set email alerts
|

An improved spectral decomposition flexibility perturbation method for finite element model updating

Abstract: Finite element analysis is the most powerful tool to predict the behavior of a structure in engineering practice. Generally, the initial finite element model must be corrected with experimental data due to its complexity. Thus, it is very necessary to study a finite element model updating method with high precision and high efficiency. To this end, this article presented an improved spectral decomposition flexibility perturbation method for structural finite element model updating. The improvements of the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Finite element model updating is a technique to improve the prediction of the numerical simulations with the data from experimental test. In an article by Yang et al, 7 ''An improved spectral decomposition flexibility perturbation method for finite element model updating,'' the authors presented an improved technique in two aspects: (1) adopting a uniform correction model and (2) using the twice singular-valuetruncation method. A beam structure is used as a vehicle for model updating in a noisy environment, and it is reported that only the results obtained by the second singular value truncation is stable.…”
Section: Discussionmentioning
confidence: 99%
“…Finite element model updating is a technique to improve the prediction of the numerical simulations with the data from experimental test. In an article by Yang et al, 7 ''An improved spectral decomposition flexibility perturbation method for finite element model updating,'' the authors presented an improved technique in two aspects: (1) adopting a uniform correction model and (2) using the twice singular-valuetruncation method. A beam structure is used as a vehicle for model updating in a noisy environment, and it is reported that only the results obtained by the second singular value truncation is stable.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the linear approximation was adopted in the above sensitivity analysis. Reference [27] discusses the influence of the linear approximation on fault diagnosis results. It was found that the fault coefficients calculated from the linear approximation equations are always larger than the true values.…”
Section: The Hybrid Sensitivitymentioning
confidence: 99%
“…Weng et al [79] proposed a damage assessment method based on the decomposition of the substructure's flexibility and found that the characteristic parameters obtained from decomposition of the substructure's flexibility were more sensitive to structural damage. Yang et al [80] improved the method based on the perturbation of flexibility by using spectral decomposition and obtained more accurate results from the model corrected through the method of using multiple feedback and truncation of singular values. Qi et al [81] constructed a damage localization index based on lower and upper (LU) decomposition of the proportional flexibility matrix and applied it to detect damage in composite beams.…”
Section: Assessing Damage By Decomposing the Flexibilitymentioning
confidence: 99%